Regular Mechanical Stimuli Enhanced Tolerance to Salinity Stress in Glycine max L. Seedlings: Effect of Touch on Soybean - Patel, Juhika; Albert, Susy; Patlavath, Ravinayak (Journal of Tropical Life Science, 2023)
Regular touch treatment leads to plant adaptations that enhances mechanical strength. In many crop plants these adaptations result in cross-tolerance to biotic stress caused by bacterial or fungal infection and abiotic stress conditions like salinity or drought. In present study, we have explored the effect of mechanical stress on the growth of Glycine max (soybean) seedlings and studied its effect on tolerance to salinity stress. Regular mechanical stress given in the form of touch suppressed overall growth of the soybean seedlings. Touch pre-treated seedlings were further treated with sodium chloride to test for its tolerance to salinity. Upon salt treatment, we observed comparatively higher survival rate and more growth in the seedlings that received regular mechanical stress during early growth stages. The adaptations to mechanical stress given at the early-stage of growth may have led to the enhanced tolerance to salinity stress experienced in later growth stage